1997
DOI: 10.1063/1.120476
|View full text |Cite
|
Sign up to set email alerts
|

Influence of silicon-wafer loading ambients in an oxidation furnace on the gate oxide degradation due to organic contamination

Abstract: Organic contaminants adsorbed on the surface of silicon wafers do not always cause the degradation of gate-oxide integrity (GOI) degradation but very little information is available on the ambient atmosphere when wafers are loaded in an oxidation furnace. It has been found in this work that GOI is degraded when wafers having organic contamination are loaded in a nitrogen atmosphere, but that GOI degradation does not occur when the wafers are loaded in an oxygen-containing ambient. In a high-temperature nitroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
28
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 8 publications
0
28
0
Order By: Relevance
“…Because silicon is one of the technologically most important materials utilized in microelectronics, the adsorption behavior and impact of organic contaminants on silicon wafers upon storage and processing have been investigated in a systematic fashion. [17][18][19][20][21][22][23] Extending our recently published preliminary studies, 24 this paper reports comprehensive investigations of the contamination process of NH 4 F etched H-Si͑111͒ surfaces. Both n-and p-type H-Si͑111͒ were characterized systematically by using solid-state electrical measurements and infrared spectroscopy in real time during exposure to the laboratory environment.…”
mentioning
confidence: 98%
“…Because silicon is one of the technologically most important materials utilized in microelectronics, the adsorption behavior and impact of organic contaminants on silicon wafers upon storage and processing have been investigated in a systematic fashion. [17][18][19][20][21][22][23] Extending our recently published preliminary studies, 24 this paper reports comprehensive investigations of the contamination process of NH 4 F etched H-Si͑111͒ surfaces. Both n-and p-type H-Si͑111͒ were characterized systematically by using solid-state electrical measurements and infrared spectroscopy in real time during exposure to the laboratory environment.…”
mentioning
confidence: 98%
“…One is the airborne organic contamination before plasma nitridation process. Several investigations reported that airborne organic contamination can affect the reliability of gate oxide[21 [3]. It was also reported that airborne organic contamination retarded the plasma nitridation process [4].…”
Section: Introductionmentioning
confidence: 99%
“…One is the airborne organic contamination before plasma nitridation process. Several investigations reported that airborne organic contamination can affect the reliability of gate oxide [2] [3] . It was also reported that airborne organic contamination retarded the plasma nitridation process [4] .…”
Section: Introductionmentioning
confidence: 99%